Thermal control techniques for infrared imaging on nanosatellites - Shanmugasundaram Selvadurai (Nanyang Technological University, 2024)
The objective of this thesis is to design and develop innovative thermal control systems with a specific focus on micro- and nano-satellites. Considering the current advancements in technology and projected trends, nanosatellites are anticipated to play a significant role in both scientific and defense applications due to their advantages in reduced mass, cost-effectiveness, and rapid development cycles. However, as the capabilities of nanosatellites increase, the need for effective thermal control systems becomes increasingly crucial, particularly with the rising demand for high-power applications. This thesis addresses the challenge of designing thermal control systems (TCS) for active infrared devices on CubeSat platforms. The research encompasses two distinct instruments: one requiring passive cooling, designed for near-infrared imaging, and another necessitating active cooling. Nanyang Technological University (NTU) in Singapore is actively engaged in the development of the 27U ARCADE satellite project, which aims to explore Earth’s Mesosphere- Lower-Thermosphere (MLT) and conduct ground imaging from a Very Low Earth Orbit (VLEO). The primary payload for ARCADE is AtmoLITE, a near-infrared imager equipped with a CMOS detector that needs to maintain a temperature range of 0 degC to -30 degC to achieve optimal performance. To accomplish this, a passive deep space radiator is integrated with the instrument to provide the required cooling. The design of the radiator is strategically planned to minimize incoming environmental heat loads. The thesis’s scope involves validating the thermal performance of this sensor through ground-based vacuum experiments and potentially using flight data. The second part of the research focuses on developing an effective active control approach for a 6U CubeSat. Given the inherent spatial constraints, nanosatellites equipped with high-power scientific equipment, such as infrared or cryogenic instruments requiring active cooling, necessitate well-suited thermal control systems. A case in point is the Doppler Wind Temperature Sounder (DWTS), which operates optimally when actively cooled within the temperature range of 95K to 110K. In this context, a micro-cryocooler is considered as a solution to actively cool the instrument’s detector. Notably, CubeSat missions integrating cryocooler units (CCUs) are rare due to the substantial challenges associated with their implementation. This part of the research aims to develop a novel modular TCS framework for integrating CCUs within the confined volume of a CubeSat. Extensive research is conducted on Heat Pipes (HPs), Single-Phase Mechanically Pumped Fluid Loop (SPMPFL), and Two-Phase Mechanically Pumped Fluid Loop (2φMPFL) systems to determine the most effective approach, which will be further developed and refined for ground-based testing. In summary, the primary goals of this thesis involve advancing the design of thermal control systems for nanosatellites, focusing on both passive and active cooling solutions. The research spans the thermal management of a near-infrared imaging payload and the development of a modular TCS framework to accommodate a cryocooler unit in a CubeSat. Through systematic investigation and experimentation, this thesis contributes to the enhancement of thermal control strategies for cutting-edge micro- and nano-satellites, thereby promoting their effectiveness and enabling future space exploration endeavours.